Resiliansi warga di wilayah rawan banjir di Bojonegoro - Nurul Hartini (Masyarakat, Kebudayaan dan Politik, 2017)
Many residents in flood-prone areas Bojonegoro have chosen to remain occupying their house, to keep working and performing productive activities in the flood-prone areas. This phenomenon raises a question about “Resident’s resilience in flood-prone areas”. The research subjects are citizens of Bojonegoro from six flood-prone districts, namely: Dander, Bojonegoro, Kanor, Trucuk, Ngringinrejo and Baureno. Data collection is conducted by observation, interviews, and focused group discussion. This research confirmed the theory of Resilience from Grotberg (1995) on the citizens of Bojonegoro, where people living in floodprone areas have developed preparations and certain activities in order to manage the flood in their living areas every moonson.